Anti-static packaging film and preparation method thereof

By using fillers such as hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide in packaging films in synergy with antistatic dispersants, a packaging film with excellent mechanical properties, antistatic effect, and light transmittance is prepared, solving the problems of unstable antistatic ability and performance balance in the existing technology.

CN119350819AInactive Publication Date: 2025-01-24KEHENG POLYMER (GUANGDONG) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411655797.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing antistatic packaging films have unstable antistatic capabilities in complex environments, and it is difficult to balance light transmittance and mechanical properties, resulting in reduced practicality.

Method used

Using TPEE membrane, a synergistic antistatic system is formed by fillers such as hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide with antistatic dispersants. Combined with a specific ratio of polyether polyol and processing aids, a packaging film with excellent mechanical properties, antistatic effect and light transmittance is prepared.

Benefits of technology

The packaging film achieves high light transmittance (over 85%), high mechanical strength (tensile strength 30MPa, elongation at break over 740%), and low surface resistivity (below 5.0*106 ohms), ensuring the protection and display of electronic products and precision instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to an antistatic packaging film and a preparation method thereof. Comprising a TPEE film body, and the TPEE film body is prepared from the following raw materials in percentage by weight: 10-40% of terephthalic acid, 20-30% of 1, 4-butanediol, 38-54% of polyether polyol, 0.5-5% of an antistatic compound, 0.1-0.5% of a catalyst and the balance of a processing aid. The antistatic compound is obtained by mixing a filler and an antistatic dispersant in a weight ratio of 10: (2-5); the filler is composed of at least two of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide. A special antistatic system is formed by two of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide and an antistatic dispersant, an antistatic compound and a raw material system are fully and uniformly mixed, and a synergistic effect of the components is combined, so that the antistatic property of the material is improved. Therefore, the anti-static packaging film has excellent mechanical property, anti-static effect and light transmission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging films, and more specifically, to an antistatic packaging film and a preparation method thereof. Background Art

[0002] As an important material, packaging film plays a vital role in the packaging process of electronic products, precision instruments and other fields. With the continuous advancement of science and technology, people have put forward higher and higher requirements on the electrostatic performance of packaging films, because product damage caused by static electricity occurs frequently. Therefore, the research and development of anti-static packaging films has become the focus of attention of various companies and research institutions to improve the safety and reliability of products. At present, in order to prepare anti-static packaging films, it is common to improve the electrostatic properties of the film by adding antistatic agents. Common methods include adding conductive fillers or coating the surface with an antistatic layer.

[0003] For example, a layer of antistatic solution is coated on the surface of the film, and the antistatic agent molecules form a uniform conductive layer on the surface of the film to inhibit static electricity accumulation, but there is a common problem of unstable antistatic effect. Especially in complex application environments, the antistatic ability is difficult to maintain effectively for a long time, resulting in the antistatic performance of the film gradually decreasing over time.

[0004] There are also ways to add conductive fillers such as carbon black or metal powder to achieve the effect of static discharge through the good conductivity of these materials, but this will lead to a decrease in the light transmittance and mechanical properties of the anti-static packaging film, thereby reducing its practicality. Summary of the invention

[0005] In order to obtain better light transmittance, mechanical strength and antistatic properties, the present application provides an antistatic packaging film and a preparation method thereof.

[0006] An antistatic packaging film includes a TPEE film body, wherein the TPEE film body is made of the following raw materials in percentage by weight: Terephthalic acid 10-40% 1,4-Butanediol 20-30% Polyether polyol 38-54% Antistatic compound 0.5-5% Catalyst 0.1-0.5% The balance is processing aids; The antistatic composite is obtained by mixing a filler and an antistatic dispersant in a weight ratio of 10:(2-5); The filler is composed of at least two of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide.

[0007] By adopting the above technical scheme, terephthalic acid as a hard segment enhances the mechanical properties of the film; 1,4-butanediol as a chain extender improves the mechanical strength and processing performance of the film; polyether polyol as a soft segment gives the film good elasticity and toughness.

[0008] At least two fillers composed of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide are combined with an antistatic dispersant to make them evenly dispersed in the raw material system, thereby reducing the impact on the performance of the packaging film and achieving a better antistatic effect.

[0009] Hexagonal boron nitride and porous titanium dioxide have certain conductivity, while hollow mesoporous silica and porous titanium dioxide have hollow and mesoporous structures, which can effectively absorb and store moisture. Hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide white powder are mixed with antistatic dispersants in a specific weight ratio to play a synergistic antistatic synergistic role and form a special antistatic system. At the same time, the obtained antistatic composite is fully mixed with the raw material system, and combined with the synergistic effect of each component, the antistatic packaging film has excellent mechanical properties, antistatic effect and light transmittance.

[0010] The light transmittance of the packaging film obtained in this application is above 85%, which is convenient for packaging electronic products, precision instruments, etc., and the appearance of the packaged products can be clearly observed, which is convenient for display and improves its practicality; the tensile strength is 30MPa, and the elongation at break is above 740%. Its mechanical strength can reduce the phenomenon of damage to the packaging film, so that it can better protect electronic products, precision instruments, etc. The surface resistivity is 5.0*10 6 In summary, the packaging film obtained in the present application has good mechanical properties, antistatic effect and light transmittance.

[0011] Preferably, the polyether polyol is polytetramethylene ether glycol and / or polytrimethylene ether glycol.

[0012] By adopting the above technical solution, the antistatic packaging film has better mechanical strength and elasticity while maintaining excellent antistatic performance. Specifically, the polyether polyol uses polytetramethylene ether glycol and / or polytrimethylene ether glycol as the soft segment component, which improves the mechanical strength of the material, thereby enhancing the overall mechanical strength and stability of the packaging film. Reduce the possibility of breakage. In combination with other raw materials, the obtained packaging film has better mechanical properties, antistatic effect and light transmittance.

[0013] Preferably, the polyether polyol is composed of polytetramethylene ether glycol and polytrimethylene ether glycol in a weight ratio of 1:(0.3-0.6).

[0014] By adopting the above technical solution, the specific ratio of polyether polyols is optimized, thereby better balancing the elasticity and processability of the material and improving the overall performance of the film. Specifically, the use of polytetramethylene ether glycol and polytrimethylene ether glycol in a specific weight ratio helps to improve the mechanical strength and light transmittance of the TPEE film, while enhancing the antistatic effect.

[0015] Preferably, the filler is composed of hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide in a weight ratio of 1:(1-3):(1-1.5).

[0016] By adopting the above technical solution, the filler is composed of hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide in a weight ratio of 1: (1-3): (1-1.5), which effectively improves the antistatic performance and mechanical strength of the material. The conductivity of hexagonal boron nitride enhances the electrostatic discharge ability of the material, while the porous structure of hollow mesoporous silica increases the water adsorption capacity, further improving the antistatic effect. Porous titanium dioxide enhances the mechanical toughness and antistatic properties of the material. The three compounds play a synergistic role, thereby making the packaging film have better mechanical strength and antistatic effect.

[0017] Preferably, the particle size of the hexagonal boron nitride is 0.01-5 microns, the particle size of the hollow mesoporous silica is 0.01-1 microns, and the particle size of the porous titanium dioxide is 1-5 microns.

[0018] By adopting the above technical scheme, the particle sizes of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide are optimized, and the uniform dispersion and excellent antistatic performance of the antistatic packaging film under the control of micron-level particle size are achieved. At the same time, hollow mesoporous silica can effectively absorb and store moisture due to its unique pore structure, thereby enhancing the antistatic effect and environmental adaptability of the film.

[0019] Preferably, the antistatic dispersant is composed of the following raw materials in parts by weight: Poly(lactic acid-co-glycolic acid) 1-3 Dimethyldiallylammonium chloride-acrylic acid copolymer 0.1-0.3 parts Vinyl tri(β-methoxyethoxy)silane 0.5-1.8 parts Polyethylene glycol derivative 0.1-0.3 parts 3-5 parts of 1,4-butanediol.

[0020] By adopting the above technical scheme, the polylactic acid glycolic acid copolymer, dimethyldiallyl ammonium chloride-acrylic acid copolymer, and polyethylene glycol derivatives in the antistatic dispersant are all hydrophilic and easy to absorb water, which helps to improve the antistatic performance of the film; dimethyldiallyl ammonium chloride-acrylic acid copolymer, as a polymer surfactant, also has an antistatic effect; vinyl tri(β-methoxyethoxy) silane acts as a coupling agent to enhance the bonding between components; 1,4-butanediol acts as a dispersant, solvent and diluent to promote uniform mixing of the components. When the antistatic dispersant of this application is used in the TPEE film raw material system, it can further react under the action of a catalyst, so that the comprehensive performance of the obtained packaging film is better.

[0021] The compatibility and dispersibility of the filler and the raw material system can be effectively improved by using polylactic acid-hydroxyacetic acid copolymer, dimethyldiallylammonium chloride-acrylic acid copolymer, vinyltri(β-methoxyethoxy)silane, and polyethylene glycol derivatives, and the water absorption can be enhanced to form a characteristic antistatic water absorption system with the filler, so that the film has better antistatic properties, mechanical properties and light transmittance.

[0022] Preferably, the polyethylene glycol derivative is polyethylene glycol monomethyl ether maleimide and / or amino-polyethylene glycol-hydroxyl.

[0023] By adopting the above technical scheme, the specific type selection of polyethylene glycol derivatives in the antistatic dispersant is increased, which helps to improve the comprehensive performance of the antistatic dispersant, thereby enhancing the dispersibility and stability of the antistatic complex in the TPEE film, and then improving the antistatic effect of the entire antistatic packaging film.

[0024] Preferably, the antistatic dispersant is obtained by the following method: According to parts by weight, polylactic acid-glycolic acid copolymer, vinyl tri(β-methoxyethoxy)silane, polyethylene glycol derivative, dimethyldiallylammonium chloride-acrylic acid copolymer, and 1,4-butanediol were weighed and mixed evenly to obtain an antistatic dispersant.

[0025] By adopting the above technical solution, the antistatic dispersant can effectively improve the uniformity of the filler dispersion in the TPEE film, enhance the antistatic effect, and improve the mechanical properties and processing properties of the film. Specifically, the antistatic dispersant composed of polylactic acid-glycolic acid copolymer, vinyl tri(β-methoxyethoxy) silane, polyethylene glycol derivatives, dimethyl diallyl ammonium chloride-acrylic acid copolymer and 1,4-butanediol has good dispersibility and hydrophilicity, and can effectively improve the dispersion state of the filler, thereby significantly improving the antistatic performance, physical and mechanical properties and light transmittance of the TPEE film.

[0026] Preferably, the processing aid is an antioxidant and / or a defoaming agent.

[0027] By adopting the above technical solution, the processing aid is selected from one or more combinations of antioxidants, plasticizers, and defoamers, which can effectively improve the stability of the TPEE film during the processing and the performance of the final product, ensuring that the packaging film has better antistatic effect and mechanical strength during use, and has better light transmittance.

[0028] In a second aspect, a method for preparing an antistatic packaging film comprises the following steps: According to parts by weight, weigh the processing aid, polyether polyol, 1,4-butanediol and terephthalic acid, mix them evenly, heat them to 220-230°C, react for 3-5 hours to obtain TPEE semi-prepolymer, cool them to 170-180°C, add the antistatic compound and mix them evenly, continue to react for 1-3 hours, discharge the material to obtain the antistatic TPEE material; apply the antistatic TPEE material on the release film while it is hot, cool it to solidify it to form a TPEE layer on the release film, let it stand to absorb water, dry the surface, peel off the release film, and the obtained TPEE layer is a packaging film.

[0029] By adopting the above technical solution, by mixing the processing aid, polyether polyol, 1,4-butanediol and terephthalic acid and reacting them at 220-230°C for 3-5 hours, it is possible to ensure that the raw materials are evenly dispersed and fully reacted to form a TPEE semi-prepolymer, thereby improving the chemical stability of the material; subsequently, the temperature is lowered to 170-180°C and an antistatic compound is added for mixing, thereby ensuring that the compound is evenly dispersed at a lower temperature, avoiding decomposition at high temperature, and further improving the antistatic performance of the material.

[0030] Continuing the reaction for 1-3 hours helps to fully combine the antistatic compound with the substrate. After the material is discharged, it is coated on the release film while hot and cured thereon to form a TPEE layer, which can be quickly formed and maintain good surface flatness; standing to absorb water and dry the surface to form a certain humidity inside the packaging film, which helps to further stabilize the material and achieve a good antistatic effect; through strict control of the reaction conditions and environment throughout the process, a method for producing a packaging film with good antistatic properties and high stability is achieved.

[0031] In summary, this application has the following beneficial effects: 1. Two of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide are used together with antistatic dispersants to form a special antistatic system. At the same time, the antistatic composite material is fully mixed with the raw material system. Combined with the synergistic effect of each component, the antistatic packaging film has excellent mechanical properties, antistatic effects and light transmittance.

[0032] 2. The compatibility and dispersibility of the filler and the raw material system can be effectively improved by using polylactic acid-hydroxyacetic acid copolymer, dimethyldiallylammonium chloride-acrylic acid copolymer, vinyl tri(β-methoxyethoxy) silane, and polyethylene glycol derivatives, and the water absorption can be enhanced to form a characteristic antistatic water absorption system with the filler, so that the film has better antistatic properties, mechanical properties and light transmittance. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] Introduction of some raw materials; The number average molecular weights of polytetramethylene ether glycol and polytrimethylene ether glycol are both 1000-2000; The porosity of hollow mesoporous silica is 65-75%; The porosity of porous titanium dioxide is 28-38%; The molecular structure of poly(lactic acid-co-glycolic acid) is as follows: x is 5-11, y is 6-10; Dimethyldiallylammonium chloride-acrylic acid copolymer CAS No. 53694-17-0; Polyethylene glycol monomethyl ether maleimide number average molecular weight 1000-2000; The number average molecular weight of amino-polyethylene glycol-hydroxyl is 1000-2000; The antioxidant is antioxidant 1076 The defoaming agent is Evonik TEGO AIREX 902W silicone water-based defoaming agent.

[0035] Preparation Example of Antistatic Dispersant Preparation Example 1 The antistatic dispersant is obtained by the following method: Weigh 1 kg of polylactic acid-glycolic acid copolymer, 0.5 kg of vinyl tri(β-methoxyethoxy) silane, 0.3 kg of polyethylene glycol derivative, 0.3 kg of dimethyldiallylammonium chloride-acrylic acid copolymer, and 5 kg of 1,4-butanediol, put them into a stirring device and stir them at a speed of 100 r / min for 20 minutes to fully mix them to obtain an antistatic dispersant.

[0036] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used is different, as shown in Table 1; Table 1 Raw materials for preparation examples 1-3 (kg) Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 2 is that the polyethylene glycol derivative is amino-polyethylene glycol-hydroxyl.

[0037] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 2 is that the ethylene glycol derivative is composed of polyethylene glycol monomethyl ether maleimide and amino-polyethylene glycol-hydroxyl in a weight ratio of 1:0.2.

[0038] Preparation Comparative Example Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that polylactic acid-co-glycolic acid copolymer, polyethylene glycol derivative, and dimethyldiallylammonium chloride-acrylic acid copolymer are replaced by vinyl tri(β-methoxyethoxy)silane in equal amounts.

[0039] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that the polylactic acid-co-glycolic acid copolymer is replaced by 1,4-butanediol in an equal amount.

[0040] Preparation Comparative Example 3 The difference between Preparation Comparative Example 3 and Preparation Example 1 is that an equal amount of dimethyldiallylammonium chloride-acrylic acid copolymer is replaced by 1,4-butanediol.

[0041] Preparation Comparative Example 4 The difference between Preparation Comparative Example 4 and Preparation Example 1 is that the polyethylene glycol derivative is replaced by 1,4-butanediol in equal amounts. Example

[0042] Example 1 An antistatic packaging film includes a TPEE film body, which is prepared by the following method: According to the weight percentage, 1.4% processing aid, 38% polyether polyol, 20% 1,4-butanediol and 40% terephthalic acid were weighed and put into a reactor, stirred at a speed of 100 r / min for 10 minutes to mix them evenly, heated to 220°C, reacted for 4 hours to obtain TPEE semi-prepolymer, cooled to 175°C, and then 0.5% antistatic compound was added and mixed evenly, and the reaction was continued for 3 hours, and the antistatic TPEE material was obtained; the antistatic TPEE material was coated on the release film while hot, cooled to 30°C, and the release film was cured to form a TPEE layer, and then placed in an environment with a temperature of 30°C and a humidity of 85% for 3 hours to allow it to stand and absorb water, dry the surface, and form a certain humidity inside the packaging film, peel off the release film, and the obtained TPEE film body is the packaging film.

[0043] The antistatic compound is obtained by mixing a filler and an antistatic dispersant in a weight ratio of 10:2; the antistatic dispersant is obtained by mixing polyethylene glycol (number average molecular weight of 6000) and 1,4-butanediol in a weight ratio of 1:1.

[0044] Among them, the particle size of hexagonal boron nitride is 0.01-5 microns, the particle size of hollow mesoporous silica is 0.01-1 micron, and the particle size of porous titanium dioxide is 1-5 microns.

[0045] The filler is obtained by mixing hexagonal boron nitride and hollow mesoporous silica in a weight ratio of 1:1. The polyether polyol is polytetrahydrofuran ether diol. The processing aid is obtained by mixing an antioxidant and a defoamer in a weight ratio of 1:3. Example

[0046] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used is different, as shown in Table 2; Table 2 Raw material dosage of Examples 1-3 (%) Example 4 The difference between Example 4 and Example 2 is that the polyether polyol is polytrimethylene ether glycol.

[0047] Example 5 The difference between Example 5 and Example 2 is that the polyether polyol is composed of polytetramethylene ether glycol and polytrimethylene ether glycol in a weight ratio of 1:0.5.

[0048] Example 6 The same thing as Example 6 is that the filler is composed of hollow mesoporous silica and porous titanium dioxide in a weight ratio of 1:0.3.

[0049] Example 7 The difference between Example 7 and Example 5 is that the filler is composed of hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide in a weight ratio of 1:1:1.5.

[0050] Example 8 The difference between Example 8 and Example 5 is that the filler is composed of hexagonal boron nitride, hollow mesoporous silica, and porous titanium dioxide in a weight ratio of 1:3:1.

[0051] Examples 9-16 The difference between Examples 9-16 and Example 8 is that the sources of the antistatic dispersant are different, as shown in Table 3; Table 3 Sources of antistatic dispersants for Examples 9-16 Example Source of antistatic dispersant Example 9 Preparation Example 1 Example 10 Preparation Example 2 Embodiment 11 Preparation Example 3 Example 12 Preparation Example 4 Embodiment 13 Preparation Comparative Example 1 Embodiment 14 Preparation Comparative Example 2 Embodiment 15 Preparation Comparative Example 3 Example 16 Preparation Comparative Example 4 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the antistatic dispersant is replaced by filler in equal amount.

[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the antistatic compound is hexagonal boron nitride.

[0053] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the filler is hollow mesoporous silica.

[0054] Performance testing Obtain antistatic TPEE material; apply the antistatic TPEE material on a release film while hot, cool to 30°C, solidify the release film to form a TPEE layer, and then place it in an environment with a temperature of 30°C and a humidity of 85% for 3 hours to allow it to absorb water and dry its surface, so that a certain humidity is formed inside the packaging film, peel off the release film, and obtain a test sample for the following experiment.

[0055] Test method / test method Tensile strength: refer to ASTM D638, the test condition is 50mm / min, the thickness of the test sample is 2mm.

[0056] Elongation at break: refer to ASTM D638, the test condition is 50mm / min, and the thickness of the test sample is 2mm.

[0057] Light transmittance: GB / T 2410-2008 Test method for light transmittance and haze of transparent plastics.

[0058] Surface resistivity: Tested with reference to the voltage-current method in the surface resistance test method of GB / T33398-2016, with a thickness of 1 mm.

[0059] The above experiments all tested 5 test samples and then took the average value. The specific data are shown in Table 4; Table 4 Experimental data of Examples 1-16 and Comparative Examples 1-3 Combining Example 1 and Comparative Examples 1-3 and Table 4, it can be seen that the tensile strength, elongation at break, transmittance and surface resistivity of Comparative Examples 1-3 are all smaller than those of Example 1, indicating that the packaging film prepared by the raw material system of the present application generally has better mechanical strength, transmittance and antistatic properties.

[0060] Combining Example 5 and Example 7 and Table 4, it can be seen that the tensile strength, elongation at break, light transmittance and surface resistivity of Example 5 are all smaller than those of Example 7. This shows that the compound of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide has a better comprehensive effect.

[0061] Combining Example 8 and Example 9 and Table 4, it can be seen that the tensile strength, elongation at break, light transmittance and surface resistivity of Example 8 are all lower than those of Example 9. It is described that an antistatic dispersant composed of polylactic acid-hydroxyacetic acid copolymer, vinyl tri(β-methoxyethoxy) silane, polyethylene glycol derivative, dimethyl diallyl ammonium chloride-acrylic acid copolymer and 1,4-butanediol is used in a raw material system in combination with hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide, so that the packaging film has a better comprehensive effect.

[0062] Combining Example 9 and Examples 13-16 and Table 4, it can be seen that the tensile strength, elongation at break, transmittance and surface resistivity of Examples 13-16 are all smaller than those of Example 9, indicating that the antistatic dispersant composed of polylactic acid-hydroxyacetic acid copolymer, vinyl tri(β-methoxyethoxy) silane, polyethylene glycol derivative, dimethyldiallyl ammonium chloride-acrylic acid copolymer and 1,4-butanediol has a better effect and is used in the raw material system to make the packaging film have a better comprehensive effect.

[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An antistatic packaging film, characterized in that: The invention comprises a TPEE membrane body, wherein the TPEE membrane body is made of the following raw materials in weight percentage: Terephthalic acid 10-40% 1,4-Butanediol 20-30% Polyether polyol 38-54% Antistatic compound 0.5-5% Catalyst 0.1-0.5% The balance is processing aids; The antistatic composite is obtained by mixing a filler and an antistatic dispersant in a weight ratio of 10:(2-5); The filler is composed of at least two of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide.

2. The antistatic packaging film according to claim 1, characterized in that: The polyether polyol is polytetramethylene ether glycol and / or polytrimethylene ether glycol.

3. The antistatic packaging film according to claim 2, characterized in that: The polyether polyol is composed of polytetramethylene ether glycol and polytrimethylene ether glycol in a weight ratio of 1:(0.3-0.6).

4. The antistatic packaging film according to claim 1, characterized in that: The filler is composed of hexagonal boron nitride, hollow mesoporous silica and porous titanium dioxide in a weight ratio of 1:(1-3):(1-1.5).

5. The antistatic packaging film according to claim 1, characterized in that: The particle size of the hexagonal boron nitride is 0.01-5 microns, the particle size of the hollow mesoporous silica is 0.01-1 microns, and the particle size of the porous titanium dioxide is 1-5 microns.

6. The antistatic packaging film according to claim 1, characterized in that: The antistatic dispersant is composed of the following raw materials in parts by weight: Poly(lactic acid-co-glycolic acid) 1-3 Dimethyldiallylammonium chloride-acrylic acid copolymer 0.1-0.3 parts Vinyl tri(β-methoxyethoxy)silane 0.5-1.8 parts Polyethylene glycol derivative 0.1-0.3 parts 3-5 parts of 1,4-butanediol.

7. The antistatic packaging film according to claim 6, characterized in that: The polyethylene glycol derivative is polyethylene glycol monomethyl ether maleimide and / or amino-polyethylene glycol-hydroxyl.

8. The antistatic packaging film according to claim 6, characterized in that: The antistatic dispersant is obtained by the following method: According to parts by weight, polylactic acid-glycolic acid copolymer, vinyl tri(β-methoxyethoxy)silane, polyethylene glycol derivative, dimethyldiallylammonium chloride-acrylic acid copolymer, and 1,4-butanediol were weighed and mixed evenly to obtain an antistatic dispersant.

9. The antistatic packaging film according to claim 1, characterized in that: the processing aid is an antioxidant and / or a defoaming agent.

10. A method for preparing an antistatic packaging film according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the weight percentage, the processing aid, polyether polyol, 1,4-butanediol and terephthalic acid are weighed and mixed evenly, heated to 220-230°C, reacted for 3-5h to obtain TPEE semi-prepolymer, cooled to 170-180°C, and then the antistatic compound is added and mixed evenly, and the reaction is continued for 1-3h, and the material is discharged to obtain the antistatic TPEE material; the antistatic TPEE material is coated on the release film while hot, cooled to solidify the release film to form a TPEE layer, allowed to stand to absorb water, the surface is dried, and the release film is peeled off to obtain the TPEE film body as a packaging film.

Citation Information

Patent Citations

  • Graphene oxide / polyester elastomer composite material and preparation method thereof

    CN103642018A